2019
DOI: 10.1097/ncq.0000000000000378
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Safety Culture on Missed Nursing Care and Adverse Patient Events

Abstract: Background: A strong patient safety culture (PSC) may be associated with improved patient outcomes in hospitals. The mechanism that explains this relationship is underexplored; missed nursing care may be an important link. Purpose: The purpose of this study was to describe relationships among PSC, missed nursing care, and 4 types of adverse patient events. Methods: This cross-sectional study employed primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
141
2
25

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(178 citation statements)
references
References 26 publications
10
141
2
25
Order By: Relevance
“…However, when this is not possible -as documented by previous crossnational surveys on nurse staffing [13,19] in Europe and United States -the SIPI score can be used in medical departments to identify those patients that are more complex, that are at risk of dying, and that, consequently, require an increased amount of nursing care. In fact, as patients with SIPI > 50 have an increased hazard of dying, nursing surveillance is relevant to prevent failures to rescue, when severe complications can be prevented, or to assure a dignified dying, when those complications cannot be avoided [31]. Finally, the prevalence of patients with high nursing complexity (40%), was in line with the previous multi-centre Italian study in which it resulted nearly 50% [24].…”
Section: Discussionsupporting
confidence: 79%
“…However, when this is not possible -as documented by previous crossnational surveys on nurse staffing [13,19] in Europe and United States -the SIPI score can be used in medical departments to identify those patients that are more complex, that are at risk of dying, and that, consequently, require an increased amount of nursing care. In fact, as patients with SIPI > 50 have an increased hazard of dying, nursing surveillance is relevant to prevent failures to rescue, when severe complications can be prevented, or to assure a dignified dying, when those complications cannot be avoided [31]. Finally, the prevalence of patients with high nursing complexity (40%), was in line with the previous multi-centre Italian study in which it resulted nearly 50% [24].…”
Section: Discussionsupporting
confidence: 79%
“…There is also a growing body of evidence on the negative impact of inadequate staffing levels on omissions in nursing care. Missed or omitted care has been found to be associated with adverse events including pressure ulcers, medication errors, new infections, intravenous fluids running dry or leaking, poor patient safety culture, and patient falls (Dabney & Kalisch, 2015;Hessels et al, 2019;Kalisch et al, 2011Kalisch et al, , 2014. A recent survey of RNs in nursing homes found that 72% reported missing one or more necessary care tasks on their last shift due to the lack of time or resources (White & Aiken McHugh, 2019).…”
Section: Nurse Staffingmentioning
confidence: 99%
“…Another important source of information about the adequacy of staffing may come directly from reports by facility nursing staff about their workload and inability to complete their assignments including basic care, communications, and timeliness of care. [61][62][63] Missed or omitted care has been found to be associated with adverse events including pressure ulcers, medication errors, new infections, and IVs running dry or leaking. [61][62][63][64] Missed nursing care has also been found to be associated with poor patient safety culture and patient falls, a patient safety indicator.…”
Section: Missed or Omitted Care And Staff Turnover Ratesmentioning
confidence: 99%
“…[61][62][63] Missed or omitted care has been found to be associated with adverse events including pressure ulcers, medication errors, new infections, and IVs running dry or leaking. [61][62][63][64] Missed nursing care has also been found to be associated with poor patient safety culture and patient falls, a patient safety indicator. 63,64 Staffing levels, not surprisingly, predict missed nursing care and can explain the relationship between staffing levels and patient outcomes.…”
Section: Missed or Omitted Care And Staff Turnover Ratesmentioning
confidence: 99%